Blood transfusion - Salsamendi, Julia (Cirugía del Uruguay, 1973)
Risk is a significant factor in blood transfusions; however, there are no substitutes for hemoglobine in oxigen transportation. Consequently, the. author has tried to set precise indications for transfusions in surgery patients, expressing his own viewpoint. The main problems of massive transfusions are listed, with prophylactic and therapeutical indications.